Reliability factors for steel elements designed on the basis of computer numerical models - V. V. Nadolski (Vestnik MGSU)
Introduction. Today, there is an increasing reliance on computer computational models to assess the load-bearing capacity of building structures. However, a very small number of studies address issues of ensuring the reliability of the obtained results. In the current design practice, the design reliability of structures is provided by a system of partial reliability factors that take into account the uncertainty of random variable and the accuracy of the model. Therefore, fixing the values of reliability factors or the methodology for determining them in the design standards is especially important.Materials and methods. The proposed method for determining reliability factors and their values are based on the methods of reliability theory and probability theory. Statistical characteristics of random variables and accuracy of the computer model are based on the systematization, analysis and generalization of existing studies.Results. The paper presents a system of reliability factors and a method for determining them for the studied construction solutions and standardized parameters of computer models. The results of studies of statistical characteristics of the measure of accuracy of computer models are presented. The values of conversion coefficients are proposed, which allow taking into account different models of the material, the degree of discretization and the values of imperfections.Conclusions. In the field of design of building structures, two extreme cases of using computer numerical models from the position of knowledge of the studied object (for new structural solutions and for studied solutions) and two extreme cases from the position of knowledge of model parameters (validated (standardized) or non-validated (non-standardized) computer model parameters are used). Depending on the case under consideration, model verification procedures should be specified and ways to ensure design reliability should be assigned.